Modeling the effect of liquid and solid infill on elastic moduli, dispersion and attenuation in porous media - Sun, Yongyang (Curtin University, 2020)
Quantifying the effects of various pore infills on elastic moduli, dispersion and attenuation in porous media is of considerable interest. This thesis aims at developing theoretical models to explore such effects mainly in microporous media but also in nanoporous media. Poroelasticity and effective medium theories are used to conduct explorations analytically and numerically. Laboratory measurements further confirm the validity and applicability of the developed models, which indicates their potential for reservoir characterization and production monitoring.